Inhibition of hedgehog pathway reveals the regulatory role of SMO in gastric cancer cells - Zixin Yang; Yingqian Lv; Long Wang; Yong Chen; Jinzhu Han; Shan Zhao; Wei Liu (Tumor Biology)
Previous studies report aberrant activation of the hedgehog signaling pathway in the progression of various cancers. This study aimed to investigate the expressions of smoothened and downstream glioma-associated oncogene homology-1 in gastric cancer and the underlying molecular mechanisms. Here, we first detected the expression in 58 cases of primary gastric cancer tissue and matched normal tissue specimens by western blot analysis and quantitative reverse transcription polymerase chain reaction. Cell proliferation and cycle were assayed in gastric cancer cells after blocking the hedgehog pathway by lentiviral-short hairpin RNA knockdown. In vitro inhibition of hedgehog pathway resulted in decreased cell proliferation and migration. Our studies demonstrate an important role for smoothened and glioma-associated oncogene homology-1 in gastric cancer and suggest inhibition of hedgehog pathway as a novel and potent strategy to treat gastric cancer patients.